Dynamics and steady-state analysis of a consumer-resource model. (February 2023) - Yao, Ruofei; Li, Rui
Abstract: This paper is concerned with the dynamics of a consumer-resource reaction diffusion model in the heterogeneous environment, proposed by Zhang et al. (2017). We use the comparison principle to improve the ultimate bounds step by step, and show that the unique steady state is globally asymptotically stable if the resources are fully limited uniformly in space and consumer population abundance is homogeneous in space.